Systematic Procedure of Acid Leaching for Removal of Impurities from Used Abrasive Blasting Media for Powder Metallurgy Application - Jie, Yu Jun (IRC, 2017)
Abrasive blasting is the process of thrusting a stream of abrasive material onto a surface under immense pressure for various applications, one of these is to remove foreign contaminants from a surface. Shot blasting makes use of steel shots for blasting, which mainly consist of the element iron (Fe). After the process of removing impurities using shot blasting, the leftover mixture of steel shots and impurities are disposed, which is a waste of economically valuable iron material and poses negative impacts to the environment. Hence, this study aims to study the effectiveness of acid leaching method, to recover the iron from used shot blasting media. Acid leaching is an effective way to selectively isolate and recover metals from mixtures. Through an extensive research, it is found that there are various parameters which govern the effectiveness of the leaching process, namely the rate of stirring, the leached material grain size, the solid (material) to liquid (acid) ratio, type of acid, concentration of acid, leaching temperature, and leaching time duration. However, studies on the use of acid leaching on used shot blasting media have not been extensively conducted. Hence, leaching experiments have been conducted to test the effects of varying leaching durations on the recovery percentage of iron from the used shot blasting media. The research methodology is briefly outlined as follows: information gathering, background study, literature review, pre-experimental characterization, execution of leaching experiment, post-experimental characterization, results analysis and conclusion. The results show that acid leaching can effectively remove impurities from used shot blasting media and have successfully recovered 73.6% of iron on the particle surface level, and 44.3% of iron in overall. Hence, acid leaching method is a feasible technique to be used in the removal of impurities and recovery of iron from used shot blasting media. The process can be further studied and experimented to develop a procedure to achieve close to 100% recovery rate by investigating other factors in acid leaching.